(untitled) (Research, Society and Development, 2022)
This work aims to present the panorama of agents deprived of liberty (APL) and victims of violent deaths in Brazil, highlighting social characteristics and criminal types. Several studies in Brazil emphasize that crime is intrinsically related to several factors such as the use of firearms, drug trafficking and precarious urban structure. Thus, the procedures adopted to achieve the objectives of this research are descriptive and quantitative approach. Data and information were collected in the reports and documents of the Brazilian Public Security Forum, Institute of Applied Economic Research/Atlas da Violence (2021), Brazilian Institute of Geography and Statistics, National Penitentiary Department and National Penitentiary Department Information System. The findings suggest that violent crime in Brazil has characteristics and circumstances that affect all cities and victimizes several people, from children to the elderly, through homicide, robbery or bodily injury followed by death, with the use of firearms, white weapons. or aggression. The agents who commit the crimes and are in prison are adults between the ages of 18 and 34, single, self-declared brown, with low education and the highest criminal incidences are drug trafficking.